2004
DOI: 10.1081/ncn-200026046
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide—Minor Groove Binder 1:2 Conjugates: Side by Side Parallel Minor Groove Binder Motif in Stabilization of DNA Duplex

Abstract: Synthetic polycarboxamides consisting of N-methylpyrrole (Py), N-methylimidazole (Im), N-methyl-3-hydroxypyrrole (Hp) and beta-alanine (beta) show strong and sequence-specific interaction with the DNA minor groove when they form hairpin structures with side-by-side antiparallel motifs. In the present paper, new conjugates containing two ligands linked to the same terminal phosphate of DNA strand were constructed. The paper describes optimized synthesis and properties of oligonucleotide-linked polyamide strands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
(28 reference statements)
1
8
0
Order By: Relevance
“…In one of our previous publications [20], we have shown that a decrease in light absorption at 320 nm due to a shift in the absorption maximum during thermal denaturation experiments is a clear indication of the interaction and binding between dsDNA and oligocarboxamide MGBs. On the melting-curve derivatives at 320 nm, this effect is seen as a negative peak, with a minimum in a melting point of the dsDNA ± MGB complex.…”
Section: Complex Formation By Conjugates: Thermal-denaturation Studiementioning
confidence: 67%
“…In one of our previous publications [20], we have shown that a decrease in light absorption at 320 nm due to a shift in the absorption maximum during thermal denaturation experiments is a clear indication of the interaction and binding between dsDNA and oligocarboxamide MGBs. On the melting-curve derivatives at 320 nm, this effect is seen as a negative peak, with a minimum in a melting point of the dsDNA ± MGB complex.…”
Section: Complex Formation By Conjugates: Thermal-denaturation Studiementioning
confidence: 67%
“…The advantage of the amide bonds in (7) and (9) is its stability at acid pH compared to phosphoramide bond in (3) and (6). 21 In addition, we noted that products (3) and (6) do not support heating up to 55°C and degrade in thermal denaturation experiment in contrast to the conjugates (7) and especially (9).…”
Section: Dna-binding Propertiesmentioning
confidence: 78%
“…The other argument is that the natural HIV DNA fragment is the best target for molecule (9). It seems that the disposition of A/T and T/A plays an important role in bis-MGB binding and the binding blocks must be symmetrical relatively to central base pair, so that (T/A) 3-5 sequence must follow by (A/T) 3-5 sequence, as it is shown in Figure 5.…”
Section: Dna-binding Propertiesmentioning
confidence: 99%
See 2 more Smart Citations